The Angular Dependence of the Critical Current of BaCeO3 Doped YBa2Cu3O6+x Thin Films - Malmivirta M; Yao LD; Inkinen S; Huhtinen H; Palonen H; Jha R; Awana VPS; van Dijken S; Paturi P (IEEE-INST Electrical Electronics Engineers INC, 2022)
The angular dependencies of the critical current of BaCeO3 (BCO) doped YBa2Cu3O6+x (YBCO) thin films grown with pulsed laser deposition (PLD) on SrTiO3 (001) were systematically investigated. The BCO concentration in the YBCO matrix was varied between 0-8 wt.%. Transmission electron microscopy confirmed that the 4% BCO containing sample has point-like, partly agglomerated BCO particles with diameter of 2.5 nm. The dopant degrades the crystal quality of YBCO but improves its in-field current carrying performance especially at low temperatures. The BCO addition affects the angular dependence of the critical current by broadening the B parallel to ab-axis peak of YCBO but no c-axis peak is seen, which is contrary to BaZrO3 doped films made by PLD. Although the particles are point-like, it is found that a model featuring only isotropic pinning centers is not sufficient to describe the angular dependence of the samples where B parallel to ab-axis of YCBO.